The Process of Nanostructuring of Metal (Iron) Matrix in Composite Materials for Directional Control of the Mechanical Properties - Elena Zemtsova; Denis Yurchuk; Vladimir Smirnov (The Scientific World Journal)
We justified theoretical and experimental bases of synthesis of new class of highly nanostructured composite nanomaterials based on metal matrix with titanium carbide nanowires as dispersed phase. A new combined method for obtaining of metal iron-based composite materials comprising the powder metallurgy processes and the surface design of the dispersed phase is considered. The following stages of material synthesis are investigated: (1) preparation of porous metal matrix; (2) surface structuring of the porous metal matrix by TiC nanowires; (3) pressing and sintering to give solid metal composite nanostructured materials based on iron with TiC nanostructures with size 1–50 nm. This material can be represented as the material type “frame in the frame” that represents iron metal frame reinforcing the frame of different chemical compositions based on TiC. Study of material functional properties showed that the mechanical properties of composite materials based on iron with TiC dispersed phase despite the presence of residual porosity are comparable to the properties of the best grades of steel containing expensive dopants and obtained by molding. This will solve the problem of developing a new generation of nanostructured metal (iron-based) materials with improved mechanical properties for the different areas of technology.